Quality Assurance in Higher Education : A Comparison of Eight Systems - Weber, Luc; Mahfooz, Sara Bin; Hovde, Kate (World Bank, Washington, DC, 2012)
Quality in higher education is difficult to measure. Incentives to improve (or not) are often different for public and private institutions, and approaches to quality assurance have to be adapted to different situations. Poland is reforming its higher education institutional framework and the World Bank conducted a review, comparing strategies followed by (largely) Organization for Economic Cooperation and Development (OECD) countries with regard to quality assessment, to help the country assess educational services at its higher education institutions. Based on the research, some of the most comprehensive quality assessment frameworks for public universities were found in the Irish, Scottish and Hong Kong educational systems; for private universities, the Austrian and Swiss systems present interesting examples.